Taxonomic revision of the Pteronia adenocarpa group (Astereae, Asteraceae) - Bello, Anifat O.; Boatwright, James S.; van Der Bank, Michelle; Magee, Anthony R. (Phytotaxa, 2021)
This study presents a taxonomic revision of the Pteronia adenocarpa group. Six species are recognised within this group, namely P. adenocarpa, P. armatifolia, P. elongata, P. hutchinsoniana, P. stoehelinoides and P. viscosa. The group is distinct in its characteristic basally hairy cypselae, as opposed to the glabrous-glossy, glandular and/or variously hairy cypselae with the hairs evenly distributed throughout the surface found in the remaining species of the genus. We here present a detailed taxonomic treatment with descriptions, nomenclature, diagnostic characters, geographical distribution and maps, ecological information as well as the key to the species.